Analysis of Determination of Production Costs and Full Cost Recovery (a Case Study at PDAM XYZ Banda Aceh City) - Mayrazaka, Annisaa Imana; Priantana, Riha Dedi; Sayuthi, Sayuthi (Formosa Journal of Applied Sciences, 2024)
PDAM XYZ's complete cost recovery rates in 2020 and 2021 is another goal of this study. This study uses a qualitative, descriptive methodology. Primary data from interviews and secondary data from PDAM XYZ performance evaluation reports that have undergone an audit by BPKP serve as the research's data sources. The Miles & Huberman research model is the data analysis technique that is applied, consisting of data gathering, reduction, presentation, and conclusion drawing. The study's findings indicate that employing PDAM XYZ's genuine NRW yields a higher manufacturing cost than utilizing standard NRW. This study also demonstrates that, when employing the real cost of production, PDAM XYZ has not achieved the entire cost recovery rate, but, when using the standard cost of production, PDAM XYZ has achieved the complete cost recovery rate.